Marketing underutilized plant species for the poor: a case study of minor millets in Kolli hills, Tamil Nadu, India - Gruere, G.; Nagarajan, L.; Israel Oliver King. E.D. (2007)
In this paper we are conducting an evaluation of the marketing development initiative for minor millets in the Kolli Hills by the concerned non-governmental organization. We analyze the recently-created market chain of minor millet crops along with the major actors involved, through a series of field visits and focus group discussions with the relevant stakeholders. Our main objectives are (a) to identify some of the key factors that contributed to its relative success; and (b) to study the effect of the development of this market on the livelihoods of participants in the chain and on crop biodiversity. Ultimately, our analysis intends to provide insight into the relative success of conservation cum commercialization interventions for the crops concerned.